1983
DOI: 10.4319/lo.1983.28.3.0522
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing Diaptomus distributions: An experimental study in subtropical Florida1

Abstract: In central and southern Florida Diaptomus dorsalis is the sole diaptomid in most eutrophic lakes whereas Diaptomus floridanus and Diaptomus mississippiensis co‐occur in oligotrophic and mesotrophic lakes. The importance of food availability and water quality in determining the species distributions of Diaptomus was ascertained by culturing the three species in water from a lake of each type with its natural phytoplankton present and with the natural phytoplankton removed and Chlamydomonas added at a concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 22 publications
1
33
1
Order By: Relevance
“…Elmore's slow developing small species and my fast developing large species are inconsistent with theoretical predictions concerning development times and body size (Hall et al, 1976) . The correlation between distribution of Diaptomus species and trophic level which Elmore (1983) found in his studies does not hold for Boeckella nauplii . For example, D. floridanus nauplii (a species inhabiting oligotrophic-mesotrophic lakes) developed faster than D. dorsalis (a species inhabiting eutrophic lakes) in an oligotrophic-mesotrophic treatment whereas D. dorsalis nauplii developed faster in eutrophic treatments .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Elmore's slow developing small species and my fast developing large species are inconsistent with theoretical predictions concerning development times and body size (Hall et al, 1976) . The correlation between distribution of Diaptomus species and trophic level which Elmore (1983) found in his studies does not hold for Boeckella nauplii . For example, D. floridanus nauplii (a species inhabiting oligotrophic-mesotrophic lakes) developed faster than D. dorsalis (a species inhabiting eutrophic lakes) in an oligotrophic-mesotrophic treatment whereas D. dorsalis nauplii developed faster in eutrophic treatments .…”
Section: Discussionmentioning
confidence: 86%
“…In this experiment mortality was highest at colder temperatures (8 .5 and 12°C) and deaths mostly occurred among older naupliar stages . Elmore (1983) compared the development times, size and survival of three diaptomid species in a variety of food and temperature conditions . The survival and size data are only presented for complete development from egg to adult but development time data for nauplii are consistent with my observations .…”
Section: Discussionmentioning
confidence: 99%
“…Three authors to date have examined these effects: Vidal, 1980Vidal, , 1980aVidal, and 1980bWoodward andWhite, 1983 andElmore, 1983. Woodward and White worked on the same genus and found that Boeckella symmetrica copepodite development varied between 19.…”
Section: Discussionmentioning
confidence: 99%
“…1). The egg generally hatches as the first nauplius larva (Nl), and development proceeds through successive naupliar stages, maximally six in total (Nl-N6 Elmore, 1983Kamps, 1978Geiling & Campbell, 1972Munro, 1974Eckstein, 1964Weglenska, 1971 Jacobs (continued). the Dc/Dn ratio (see Table 1 for definitions and terminology) were included.…”
Section: Isochronal Development and The Dcldn Ratiomentioning
confidence: 99%